Chemical modification of N-methylphenothiazine to lead to interesting and potential organic material for lithium battery. (1st April 2017) - Guilmin, Romain; Alloin, Fannie; Molton, Florian; Leprêtre, Jean-Claude
Abstract: Human activity generates an environmental impact increasingly important including in the field of transport and portable electronics. It is therefore essential to develop of new technologies capable of producing and storing electrical energy. In this context, organic material based battery can constitute an interesting alternative compared to inorganic ones. Less costly and toxic and allowing to involve other alkali cation (rather than Li + ), since few years such materials are evoked in literature. However, their performance yet do not compete with that of involving inorganic cathodic material (i.e. Lithium iron phosphate). In this context, multi electron process can be the way to reach high performance organic compounds. This can be done using phenothiazine which, through an adapted chemical modification, can undergo a two electron oxidation in the potential window stability of classical electrolyte. This work is dedicated to the impact of N-methyl-phenothiazine chemical modification on its electrochemical behavior. The stability of oxidized forms of modified phenothiazine is investigated helping to select the best monomer to be involved as cathodic polymer material in battery.